Model Deteksi Dini Penyebaran Organisme Pengganggu Tanaman dengan Sistem SMS GATEWAY pada Kelompok Tani - Eko Subyantoro; Imam Asrowardi (Jurnal Ilmiah ESAI, 2015)
Pest is an obstacle to world agriculture, spread can occur very quickly if too late to be controlled. The government has provided extension field as a builder of farmers in crop management field, pest management to monitor the progress of growth and yield of agricultural cultivation. The limited amount of extension is not proportional to the area of cultivation so that in case of pests likely to be too late to get information and also late in handling. Agricultural information system that is easily used by farmers to inform the incidence of pests and diseases.Through early detection system based on SMS Gateway can inform farmers pest attack by sending an SMS to the system, then the system automatically forward the information to the extension to be reviewed shortly. Besides instant information delivered agricultural office to get a recording of data spread of agricultural pests, so that the future can be taken preventive measures against the spread of plant pests.Â Keyword : Early detection, intruder plant organisms, information systems, SMS Gateway